P14 Does Vitamin D Axis have an effect on the severity of Asthma?. (16th November 2010) - Sathyamurthy, R; Manney, S; Wood, A; Perkins, G; Webster, C; Krishna, MT; Mansur, AH
Abstract : Background: Vitamin D (VD) has been suggested to play a role in the development of asthma and frequency of asthma exacerbation1 . Vitamin D Binding Protein (VDBP) is thought to influence the development of COPD through its immunomodulatory effect2 . This study explores the role of vitamin D axis in relation to asthma severity. Method: An observational case control study with a healthy group (H) and subgroups of severity of asthma – steroid 'naïve' mild asthma (MA), severe asthma (SA), severe asthma dependent on oral corticosteroids (SACS) and 'type 1 brittle' asthma (BA1) was conducted. VD, VDBP, spirometry, Fractional exhaled nitric oxide (FeNO) and exacerbations requiring oral corticosteroids/year (E) were recorded in all the patients. The data were analysed by Kruskal Wallis and Spearmans rank correlation test. The study was conducted between July 2009 and April 2010. Results: Sixty subjects [16M; mean age: 39 years (19–57)] were recruited into this study. The parameters measured are shown in Abstract P14 Table 1 . We observed no significant difference in serum VD between the healthy group and any of the asthma subgroups (p=0.52), or indeed between all asthmatics grouped together and healthy controls. Similarly, there was no significant difference in serum VDBP between any of the above groups (p=0.52). VD or VDBP serum levels did not correlate with exacerbations (rs =0.08, p=0.28 for VD and rs =−0.04, p=0.76 for VDBP), FEV1, or FeNO. Conclusion: VD and VDBP level in various asthma groups, did not differ significantly from healthy volunteers in this cohort, and did not correlate with lung function, asthma exacerbations, or exhaled nitric oxide. We conclude that vitamin D axis may not play a significant role in asthma severity or exacerbations although a small effect could not be excluded which would require a larger study for confirmation.